Field appraisal of stable neem pesticide tetrahydroazadirachtin-A against mustard aphid (Lipaphiserysiml) - DHINGRA, SWARAN; SHARMA, DEEPIKA; WALIA, SURESH; KUMAR, JITENDRA; SINGH, GYANENDRA; SINGH, SHIVENDRA; JAYARAMAN, B; PARMAR, BALRAJS (The Indian Journal of Agricultural Sciences, 2011)
In a field evaluation on mustard crop (Brassicajullcea), Thermo and photostabie tetrahydroazadirachtin-A provided superior control of mustard aphid (Lipaphis erysirni Kalt.) as compared to azadirachtin. Oxydemeton-methyl, providing 88.73 % reduction in aphid population was the most effective followed by tetrahydroazadirachtin that provided 64.02 % reduction over untreated control. NeenlAzal® and neem oil EC (25 per cent) were the least effective, recording 17.1 and 7.28 % reduction in aphid population respectively over untreated control. The coccinellid beetle (Coccinella septelJlpunctata) population was the maxinlum in tetrahydroazadirachtin treatment followed closely by azadirachtin and Inininlum in oxydenleton-methyl, neem oil EC and NeenlAzal. Besides being effective against the mustard aphid, high safety 111argin to the predator was exhibited by aza-A and THA .